2020
DOI: 10.1093/jas/skaa203
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the vasoactive effects of the (S)-epimers of ergot alkaloids in vitro

Abstract: Abstract Ergot alkaloids are produced by the fungus Claviceps purpurea and their levels are carefully monitored in animal and human diets due to their harmful effects and widespread contamination of cereal crops. Ergot alkaloids exist in two forms known as the (R) and (S)-epimer with only the former being monitored in diets in North America. The (S)-epimers of ergot alkaloids are thought to be biologically inactive and, therefore, harmless. A major mechanism by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Arteries were collected, as described previously ( Cherewyk et al, 2020 ). Twelve healthy steers (15–30 mo old) of mixed breed were euthanized at a local abattoir with a single animal being killed during each visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arteries were collected, as described previously ( Cherewyk et al, 2020 ). Twelve healthy steers (15–30 mo old) of mixed breed were euthanized at a local abattoir with a single animal being killed during each visit.…”
Section: Methodsmentioning
confidence: 99%
“…The S -epimers of ergot alkaloids have been denoted as non or less bioactive compared to their corresponding R -epimers ( Smith and Shappell, 2002 ; Klotz, 2015 ). Recently, the S -epimers demonstrated biological activity, causing vascular contractility in isolated bovine vascular rings ( Cherewyk et al, 2020 ). Investigating the potential sustained contractile response of S -epimers could further evaluate their biological activity ( Mulac et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that the S-epimers of ergot alkaloids are vasoactive causing vasoconstriction of bovine dorsal metatarsal arteries in vitro [37]. It is, therefore, possible that the effects seen in this study are related to the combined activity of the R and S epimers and not just the R-epimers.…”
Section: Discussionmentioning
confidence: 58%
“…The dose-dependent decrease in contractility after pre-incubation with ERV and the occurrence of this effect at a very low dose (1 × 10 −10 M) was evidence that the effect of ergot alkaloids on blood vessels is mediated by both the dose and the time that the receptors are exposed. Without previous exposure, the ergopeptine ergot alkaloids normally reduce the contractility of vessels at concentrations higher than 1 × 10 −7 to 1 × 10 −6 M [4,22,23], which are considerably higher than the ergovaline levels expected in plasma of ruminants consuming ergot alkaloids [24]. The difference in the concentration of ergot alkaloids and the observed responses in the literature indicates that the duration of exposure can influence the ergot alkaloid effect.…”
Section: Discussionmentioning
confidence: 91%